Memory in times of war, the sign of an absence - Uribe, María Victoria (Estudios de Filosofía, 2008)
I am going to start by quoting Reyes Mate who considers that every thought looks from somewhere, is situated. There is no thought without experience or without your location. This assertion is imperative for contemporary anthropology so concerned with making explicit the place from which it is spoken or written. As an anthropologist dedicated to the study of violence and memory, I want to make explicit the place from which I am going to speak and to whom I intend to question. The horizon from which I make the following considerations is that of the barbarism that has characterized the war in Colombia. I understand by barbarism some atrocious practices such as forced disappearance, torture, individual and collective murder and dismemberment, practices that I have been studying for nearly thirty years. Although my current reflections have as a point of reference the victims of the armed conflict, I do not want to speak conceptually about them, nor do I pretend to speak for them. Rather, I would like to examine the context in which family members and survivors struggle to preserve the memories of violent events that split their lives in two. [Fragment]